THE TALE OF THE TWO LANGUAGES: THE QUEST IN UNDERSTANDING STUDENTS TOWARD ORAL COMMUNICATION - Nurul Nazira Hamzah; Nor Ain Manap (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This study investigates how students with basic English and Arabic language proficiency from the foreign language perceive their oral communication challenges in completing their oral project for Oral Communication in English and Arabic Language Level 3 - Interviewing Native/Second language speakers in the target language. Qualitative research using the case study method was adopted. A total of 74 Arabic students & English were taken for this study is on purposeful sampling. Students were required to present a short reflective journal on their view of their project at the end of the semester to the teacher-researcher. Major findings indicate that students generally held a positive view towards the idea of approaching native speakers to practice the languages. Finally, to maximize the potential of the students, it is suggested that a need analysis should be conducted at the beginning of the semester to understand the needs and preferences of students when using the languages orally both inside and outside the campus, formal and informal use. Teachers should also try to utilize the potential of the mixed-ability group to enhance peer learning and sharing.